Glucagon-Like Peptide-1 Excites Firing and Increases GABAergic Miniature Postsynaptic Currents (mPSCs) in Gonadotropin-Releasing Hormone (GnRH) Neurons of the Male Mice via Activation of Nitric Oxide (NO) and Suppression of Endocannabinoid Signaling Pathways - Farkas, Imre (Front Cell Neurosci, 2016)
Glucagon-like peptide-1 (GLP-1), a metabolic signal molecule, regulates reproduction, although, the involved molecular mechanisms have not been elucidated, yet. Therefore, responsiveness of gonadotropin-releasing hormone (GnRH) neurons to the GLP-1 analog Exendin-4 and elucidation of molecular pathways acting downstream to the GLP-1 receptor (GLP-1R) have been challenged. Loose patch-clamp recordings revealed that Exendin-4 (100 nM–5 μM) elevated firing rate in hypothalamic GnRH-GFP neurons of male mice via activation of GLP-1R. Whole-cell patch-clamp measurements demonstrated increased excitatory GABAergic miniature postsynaptic currents (mPSCs) frequency after Exendin-4 administration, which was eliminated by the GLP-1R antagonist Exendin-3(9–39) (1 μM). Intracellular application of the G-protein inhibitor GDP-β-S (2 mM) impeded action of Exendin-4 on mPSCs, suggesting direct excitatory action of GLP-1 on GnRH neurons. Blockade of nitric-oxide (NO) synthesis by Nω-Nitro-L-arginine methyl ester hydrochloride (L-NAME; 100 μM) or N(5)-[Imino(propylamino)methyl]-L-ornithine hydrochloride (NPLA; 1 μM) or intracellular scavenging of NO by 2-(4-carboxyphenyl)-4,4,5,5-tetramethylimidazoline-1-oxyl-3-oxide (CPTIO; 1 mM) partially attenuated the excitatory effect of Exendin-4. Similar partial inhibition was achieved by hindering endocannabinoid pathway using cannabinoid receptor type-1 (CB1) inverse-agonist 1-(2,4-dichlorophenyl)-5-(4-iodophenyl)-4-methyl-N-(1-piperidyl) pyrazole-3-carboxamide (AM251; 1 μM). Simultaneous blockade of NO and endocannabinoid signaling mechanisms eliminated action of Exendin-4 suggesting involvement of both retrograde machineries. Intracellular application of the transient receptor potential vanilloid 1 (TRPV1)-antagonist 2E-N-(2, 3-Dihydro-1,4-benzodioxin-6-yl)-3-[4-(1, 1-dimethylethyl)phenyl]-2-Propenamide (AMG9810; 10 μM) or the fatty acid amide hydrolase (FAAH)-inhibitor PF3845 (5 μM) impeded the GLP-1-triggered endocannabinoid pathway indicating an anandamide-TRPV1-sensitive control of 2-arachidonoylglycerol (2-AG) production. Furthermore, GLP-1 immunoreactive (IR) axons innervated GnRH neurons in the hypothalamus suggesting that GLP-1 of both peripheral and neuronal sources can modulate GnRH neurons. RT-qPCR study confirmed the expression of GLP-1R and neuronal NO synthase (nNOS) mRNAs in GnRH-GFP neurons. Immuno-electron microscopic analysis revealed the presence of nNOS protein in GnRH neurons. These results indicate that GLP-1 exerts direct facilitatory actions via GLP-1R on GnRH neurons and modulates NO and 2-AG retrograde signaling mechanisms that control the presynaptic excitatory GABAergic inputs to GnRH neurons.